Impact of Remittance on Economic Activities in Yangwarak Rural Municipality, Panchthar (Research Journal, 2024)
The study aims to explore the impact of remittance on economic activities of the households in Yangwarak Rural Municipality of Panchthar District. In the study area, remittance is a main source of income. For this purpose, 60 immigrant households were selected as sample in Phalaicha. The required data and information were collected from field survey with the help of structured questionnaire through direct interview schedule of sampled households. Descriptive statistics is carried out to analyse the collected data and information. The study found that there is an improvement in the economic status of migrant households, involvement of households in community development activities, and participation in social organization. It is concluded that it has brought a qualitative change in socio-economic status of members of households in foreign employment. The economic status of the sampled households is better than that of before receiving remittance. There are positively changes in the overall economic status of the migrant households.